Metabolic syndrome and dyslipidemia among Nigerians with lichen planus: A cross-sectional study - Ifeanyi Chibuzor Okpala; Adeolu Oladayo Akinboro; Ifeanyi Ogochukwu Ezejoifor; Abel N Onunu; Benson Uchechukwu Okwara (Wolters Kluwer Medknow Publications, 2019)
Background: Lichen planus (LP) is an inflammatory skin disease of unknown etiology associated with chronic inflammation, oxidative stress induction, and cardiovascular risk factors. Objectives: To document the prevalence of metabolic syndrome (MetS), dyslipidemia, and associated factors in Nigerian patients with LP. Methods: A cross-sectional design was made to evaluate 90 patients with LP and 90 controls for MetS and dyslipidemia in two Nigerian teaching hospitals. Diagnosis of LP was made with the aid of histology, and MetS and dyslipidemia were diagnosed using the National Cholesterol Education Program Adult Treatment Panel III criteria. Results: The prevalence of MetS was insignificantly higher in LP than in control (18.9% vs. 13.5, P = 0.311), and dyslipidemia was significantly associated with LP (60% vs. 40%, P = 0.007). LP was associated with higher mean of serum triglyceride (1.21 ± 0.34 vs. 1.08 ± 0.32 mmol/L, P = 0.003), low-density lipoprotein cholesterol (3.47 ± 0.89 vs. 3.12 ± 0.77 mmol/L, P = 0.007), and T-cholesterol (5.32 ± 0.88 vs. 4.92 ± 0.86, P = 0.002). LP patients with MetS were older (P < 0.001) and less likely to have Wickham's striae (P = 0.028) compared to those without MetS. Female LP patients were older (P = 0.047), obese (P = 0.043), and had insignificant increase in MetS prevalence compared to the males. Hypertrophic LP was more frequent in patients with dyslipidemia (63.0% vs. 27.8%, P = 0.002), and the family history of diabetes mellitus (DM) was an independent predictor of MetS in LP patients (odds ratio: 4.4, confidence interval: 1.0-19.1, P = 0.047). Limitation: Availability of fund is a significant factor that limited the sample size to the minimum required as always in a poor-resource setting. Conclusions: LP has an insignificant association with MetS and a significant association with dyslipidemia among Nigerians. The family history of DM is an independent predictor of MetS in LP patients. LP patients should be routinely screened for MetS and its components.